Test Activity Spice Traditional Balinese "Basa Genep" Against Growth Escherichia Coli During Storage on Temperature Room: Bumbu basa genep - I A.A Made Semariyani; Yasniana Dalima Dalima; Ni Made Ayu Suardani Singapurwa; I Putu Candra; I Wayan Sudiarta (SEAS (Sustainable Environment Agricultural Science), 2024)
This study aims to determine the characteristics of "Basa Genep" seasoning during storage at room temperature, to determine the shelf life of "Basa Genep" seasoning stored at room temperature, this study used a simple Randomized Complete Design (CRD), with descriptive microbial observations and shelf life observations. To determine the effect of each treatment, objective observations will be made (chemical analysis test of pH, moisture content, and microbiological analysis test of TPC, and Echerichia coli). And subjective observations are organoleptic testing). storage treatment produces even wet seasoning characteristics with total plate count (TPC) 2.3 x 103 colonies/gram, Escherihia coli 4.4 x 102 colonies/gram, 48.60% moisture content, pH test 5.66, with storage for 25 days at room temperature.